2019
DOI: 10.1097/cce.0000000000000061
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis Immunometabolism: From Defining Sepsis to Understanding How Energy Production Affects Immune Response

Abstract: Objectives: This review will examine current definitions and trends in sepsis management as well pathophysiologic mechanisms in animal and ex vivo studies that correlate decreased energy production with deranged inflammatory response during the septic process. Data Sources: The latest articles in the literature that focus on the role of immunometabolism and associated mechanisms in sepsis were selected. Study Selection:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 92 publications
0
32
0
Order By: Relevance
“…Metabolic processes regulate the immune system during normal physiology, but these effects may be amplified during severely pathologic processes such as those which occur during sepsis. Failure to consider the role of metabolic dysfunction during sepsis may contribute to the lack of success in translational sepsis research ( 48 ). This section briefly discusses potential sex-dependent differences in the immune response and metabolic processes that may contribute to sex-dependent differences in sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic processes regulate the immune system during normal physiology, but these effects may be amplified during severely pathologic processes such as those which occur during sepsis. Failure to consider the role of metabolic dysfunction during sepsis may contribute to the lack of success in translational sepsis research ( 48 ). This section briefly discusses potential sex-dependent differences in the immune response and metabolic processes that may contribute to sex-dependent differences in sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperinflammation observed in the acute phase of sepsis has been linked to metabolic changes such as energy deprivation, increased metabolic demand, and end-organ failure. The impairment of oxidative phosphorylation and the subsequent metabolic shift toward glycolysis are thought to be due to decreased expression of peroxisomal proliferator-activated receptor (PPAR)-γ (which mediates lipid and glucose metabolism) and impaired mitochondrial function (critical for oxidative phosphorylation and cell metabolism) ( 48 , 58 , 59 ). Interestingly, preclinical studies demonstrated that mitochondria in females have lower levels of oxidative stress (which was suppressed by ovariectomy) and higher levels of antioxidants and antioxidant enzymes ( 60 , 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…Immunometabolic pathways are modulated in part by the peroxisome proliferator-activated receptors (PPARs). These proteins are members of the nuclear receptor superfamily of transcriptional regulators and essential to glucose and lipid homeostasis [ 50 ]. PPARβ/δ and PPARγ play an important role in macrophage polarization [ 51 ].…”
Section: Therapeutic Approaches For Covid-19 In Patients With Metabolmentioning
confidence: 99%
“…In a mouse model, knockout of PPARγ increased IL-1β, IL-6, and TNF-α when exposed to lipopolysaccharide [ 52 ]. Unlike purely anti-inflammatory treatments, drugs targeting PPARs can have a dual effect on both immune and metabolic pathways [ 50 ]. Thiazolidinediones such as rosiglitazone and pioglitazone, both PPARγ agonists, improve cardiac function and overall mortality in animal models of sepsis and decrease the local inflammatory response by lowering IL-1β, TNF-α, and IL-6 levels [ 53 , 54 ].…”
Section: Therapeutic Approaches For Covid-19 In Patients With Metabolmentioning
confidence: 99%
“…Over the years several clinical trials of anti-inflammatory therapies such as the use of corticosteroids, activated protein C, tumor necrosis factor receptor Fc (TNFR-Fc) fusion protein, anti-tumor necrosis factor α (anti-TNF-α), thrombomodulin, and anti-interleukin1 receptor antagonist (IL-1ra) have failed to demonstrate the improvement of mortality [ 6 , 7 , 8 , 9 ]. With regards to immunomodulatory therapies to reverse immune paralysis, administration of IL-7 and inhibition of programmed cell death protein 1/programmed death ligand (PD-1/PD-L) interaction are promising investigational drugs, although their clinical effectiveness has yet to be shown [ 10 , 11 ]. On the other hand, granulocyte-macrophage colony-stimulating factor (GM-CSF) therapies have shown an effect to improve symptoms of adult patients with severe sepsis or cirrhosis by restoring innate immune responses [ 12 , 13 ] and pediatric patients with multiple organ dysfunction syndrome (MODS) by preventing nosocomial infection [ 14 ].…”
Section: Introductionmentioning
confidence: 99%